2010
DOI: 10.1037/a0017683
|View full text |Cite
|
Sign up to set email alerts
|

Thinking about the weather: How display salience and knowledge affect performance in a graphic inference task.

Abstract: Three experiments examined how bottom-up and top-down processes interact when people view and make inferences from complex visual displays (weather maps). Bottom-up effects of display design were investigated by manipulating the relative visual salience of task-relevant and task-irrelevant information across different maps. Top-down effects of domain knowledge were investigated by examining performance and eye fixations before and after participants learned relevant meteorological principles. Map design and kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
129
2
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 171 publications
(142 citation statements)
references
References 70 publications
8
129
2
3
Order By: Relevance
“…More recently, cartographic design conventions have been empirically assessed and found to be working as predicted Hegarty et al, 2010), including the principles for the systematic application of color in maps (Brewer, 1994), and statistical data representations (Brewer, 1999). Neuroimaging could take these long-standing and successful mapping principles and data visualization conventions as a starting point.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, cartographic design conventions have been empirically assessed and found to be working as predicted Hegarty et al, 2010), including the principles for the systematic application of color in maps (Brewer, 1994), and statistical data representations (Brewer, 1999). Neuroimaging could take these long-standing and successful mapping principles and data visualization conventions as a starting point.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work has repeatedly demonstrated that detailed physical properties and relations-and the perceptual systems that process them-play an important role in reasoning using visual displays in a variety of abstract contexts including puzzles (Patsenko & Altmann, 2010), biological taxa (Novick & Catley, 2007), weather diagrams (Hegarty Canham, and Fabrikant 2010), and algebra (Kirshner, 1989). …”
Section: Introductionmentioning
confidence: 99%
“…The building of a coherent mental model from animations is largely determined by learners' prior knowledge and visuospatial ability, which have top-down and bottom-up influences on processing respectively (Baddeley & Hitch, 1974;ChanLin, 2001;Hegarty & Kriz, 2008;Hegarty, Canham, & Fabrikant, 2010;Kriz & Hegarty, 2004, 2007Kalyuga, 2008;Rieber, 1991). Both factors influence how learners explore and extract visual information from the displays (Hegarty et al, 2010;Lowe, 2003).…”
Section: Moderator Factors Influencing Learning From Animationmentioning
confidence: 99%